Effectiveness of individualistic and cooperative teaching strategies in learning geometry and problem solving in mathematics among junior secondary schools (2003)
This study sought to ascertain problem solving in mathematics using cooperative and individualistic strategies in teaching and learning Geometry among Junior Secondary Schools. A sample size of one hundred students from three secondary schools in Ibadan North Local Government was used. These students were grouped into control, cooperative and individualistic teaching strategies groups, in which it was set up to test the effectiveness of the individualistic and cooperative teaching strategies. The instruments used were two teaching strategies packages Mathematics Achievement test in Geometry and students attitude inventory in Mathematics, t-test, ANOVA were used in the analysis of the data collected. 'The results of the study show that there is a significant difference in the cooperative and individualistic groups to conventional teaching method.